(untitled) (Derna Academy Journal for Applied Sciences, 2024)
Background: Vitamin D plays a critical role in bone metabolism, immune regulation, and oral tissue health. Deficiency has been linked to impaired bone healing, increased susceptibility to infection, and reduced success of oral surgical procedures. Despite abundant sunlight in Libya, hypovitaminosis D remains widely reported. This study aimed to evaluate the prevalence and distribution of vitamin D deficiency among patients attending the Oral Surgery Clinic in Surman. Methods: A descriptive cross-sectional study was conducted from March to November 2022, including 62 patients aged 14 years and above. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured and categorized as deficient (<20 ng/mL), insufficient (20–30 ng/mL), or normal (>30 ng/mL). Data were analyzed using SPSS version 21, with descriptive statistics, independent t-test, Chi-square test, and one-way ANOVA applied where appropriate. Results: The study population comprised 62.90% females and 37.10% males, with a mean age of 38.80 ± 17.57 years. The mean serum vitamin D level was 22.85 ± 9.72 ng/mL, indicating an overall tendency toward insufficiency. Vitamin D deficiency (<20 ng/mL) was observed in 35.5% of patients, insufficiency (20–30 ng/mL) in 45.2%, while only 19.4% had normal levels. No statistically significant differences were found between males and females regarding vitamin D levels (p = 0.072), nor across age groups (p = 0.715). Conclusion: Vitamin D deficiency and insufficiency are highly prevalent among patients attending oral surgery clinics in Surman, regardless of age or gender. Given vitamin D’s essential role in bone healing and surgical outcomes, routine screening and appropriate management may enhance postoperative recovery and improve oral surgical care. Further studies are recommended to assess the clinical impact of correcting vitamin D deficiency prior to oral surgical interventions